APPLIED ORTHOGONAL EXPERIMENT DESIGN FOR THE OPTIMUM MICROWAVE-ASSISTED EXTRACTION CONDITIONS OF POLYSACCHARIDES FROM RHODIOLAE RADIX - Li, Fenglin; Xiao, Furen; Gong, Jingli; Yu, Tian (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
An experiment on polysaccharides from Rhodiolae Radix (PRR) extraction was carried out using microwave-assisted extraction (MAE) method with an objective to establish the optimum MAE conditions of PRR. Single factor experiments were performed to determine the appropriate range of extraction conditions, and the optimum conditions were obtained by using orthogonal experiment design. The results showed that the optimum MAE conditions of PRR were as follows: solid-liquid ratio of 1:45 g/mL, irradiation power of 480 W, and irradiation time of 8 min, while extraction yield of PRR was 3.24 %.